Dermoscopic findings in an early malignant fibrous histiocytoma on the face - Gabriel Salerni; Carlos Alonso; German Sanchez-Granel; Mario Gorosito (Mattioli1885, 2017)
Malignant fibrous histiocytoma (MFH), currently classified as undifferentiated pleomorphic sarcoma, is the most frequent soft tissue sarcoma in adulthood, but it is not as common as a primary skin tumor. MFH affects mostly the thighs and trunk, head and neck is an infrequent presentation in adults. MFH is often diagnosed in advanced stages, with a tendency to local recurrence and systemic metastasis. Since tumor thickness and size are identified as major prognostic factors, early recognition becomes crucial to improve prognosis. We present a case of a cutaneous malignant fibrous histiocytoma located on the face in which dermoscopy was useful in clinical management and definition.